The Measurement and Correction of the Periodic Error of the LX200-16 Telescope Driving System - Jang Hae Jeong; Young Sam Lee; Chung Uk Lee (Journal of Astronomy and Space Sciences, 2000)
We examined and corrected the periodic error of the LX200-16 Telescope driving system of Chungbuk National University Campus Observatory. Before correcting, the standard deviation of the periodic error in the direction of East-West was = 7.''2. After correcting,we found that the periodic error was reduced to = 1.''2.